Financial Experience: Langkah Awal Menuju Financial Management Behavior yang Baik - Lia Arfanita; Mohammad Yunies Edward (Widya Manajemen, 2026)
Financial management behavior is essential for SME owners to develop their businesses, and financial experience plays an important role in shaping good financial management behavior. This study was conducted to examine the impact of financial experience and financial self-efficacy on financial management behavior using financial literacy and emotional intelligence as mediators. This study was quantitative in nature. A non-probability sampling method was applied using purposive sampling. The population consisted of small and medium business owners in Jepara. Data were obtained from questionnaires and analyzed using Smart PLS 3.0. The results showed that financial experience, financial literacy, and emotional intelligence had a positive impact on financial management behavior, but financial self-efficacy did not have an impact, although it could have an impact when mediated by emotional intelligence. Financial literacy was able to mediate the relationship between financial experience and financial management behavior